2020
DOI: 10.3390/ma14010139
|View full text |Cite
|
Sign up to set email alerts
|

Design of Eutectic Hydrated Salt Composite Phase Change Material with Cement for Thermal Energy Regulation of Buildings

Abstract: An energy-efficient eutectic hydrated salt phase change material based on sodium carbonate decahydrate and disodium hydrogen phosphate dodecahydrate (SD) was prepared. Then, SD was encapsulated into expanded graphite (EG) to produce form-stable composite phase change materials (SD/E), which indicated a positive effect on preventing the leakage of SD, decreasing the supercooling and improving the thermal conductivity. SD/E was further tested for thermal efficiency by simulating the indoor environment with a hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Alternatively, they demonstrated that modifying EG with an organic surfactant (trtonX-100) could also create hydrophilic surfaces, which are critical to achieve a large adsorption capacity of hydrated salts. They found that 1:10 was an optimum mass ratio of TriotonX-100 to EG for achieving the highest adsorption capacity of MgCl As shown in Figure 8b, Li et al [92] transformed expandable graphite into EG through high-temperature treatment at 800 °C and impregnated the eutectic hydrated 8b reprinted/adapted with permission from Ref. [92].…”
Section: Hydrated Salt-eg Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, they demonstrated that modifying EG with an organic surfactant (trtonX-100) could also create hydrophilic surfaces, which are critical to achieve a large adsorption capacity of hydrated salts. They found that 1:10 was an optimum mass ratio of TriotonX-100 to EG for achieving the highest adsorption capacity of MgCl As shown in Figure 8b, Li et al [92] transformed expandable graphite into EG through high-temperature treatment at 800 °C and impregnated the eutectic hydrated 8b reprinted/adapted with permission from Ref. [92].…”
Section: Hydrated Salt-eg Compositesmentioning
confidence: 99%
“…They found that 1:10 was an optimum mass ratio of TriotonX-100 to EG for achieving the highest adsorption capacity of MgCl As shown in Figure 8b, Li et al [92] transformed expandable graphite into EG through high-temperature treatment at 800 °C and impregnated the eutectic hydrated 8b reprinted/adapted with permission from Ref. [92]. 2021).…”
Section: Hydrated Salt-eg Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of porous materials to adsorb PCMs into the pore structure has been proven to be a simple and effective solution to the problem of liquid leakage [ 26 , 27 , 28 ]. Wu et al [ 29 ] selected expanded graphite to adsorb eutectic hydrated salts. It was found that expanded graphite not only prevented the leakage of hydrated salts, but also reduced the supercooling degree of hydrated salts.…”
Section: Introductionmentioning
confidence: 99%
“…(Gao et al , 2003). Wu et al (2006) studied the feasibility of using paraffin (PA) to simulate the thermal infrared characteristics of the corresponding heating parts of the tank. In the experiment, 300 g of PA was wrapped in an aluminum box to make a thermal module, which was melted by heating with a low-voltage electric heating plate.…”
Section: Introductionmentioning
confidence: 99%